Вплив структури заповнення зразків при 3D друку на їх міцність - Зимогляд, Андрій Юрійович; Гуда, Антон Ігорович; Ткаченко, Станіслав Олександрович (Український державний університет науки і технологій, ННІ ≪Дніпровський металургійний інститут≫, ІВК ≪Системні технології≫, Дніпро, 2025)
UKR: У статті описано дослідження впливу структури заповнення 3D деталі на механічну міцність. Параметр заповнення (Infill) впливає на міцність та механічні властивості отриманого тривимірного об'єкта більше за інші. Тому саме цей параметр було досліджено в цій статті, її вплив на міцність надрукованої деталі. У роботі було проведено дослідження впливу структури заповнення на механічні властивості деталі та проведено серію дослідів. Усього було перевірено 5 структур, а саме: зірка, клітинка, лінії, сітка та трикутник. За допомогою створеного устаткування, описаного у статті було проведено низька дослідів. По отриманим даним можна зробити висновок, що деталі з заповненням трикутниками і зірками мають більшу механічну міцність, ніж лініями, сітками і клітинками. Також на цих заповненнях достригається більший модуль пружності.

ENG: Additive manufacturing technologies, and in particular 3D printing, are a form of additive manufacturing technology where a three-dimensional object is created by applying successive layers of material (printing, growing) based on a digital model. Printing is performed by a 3D printer, which creates a physical object by successively applying plastic material based on a virtual 3D model. 3D printers are typically faster, more affordable, and easier to use than other additive manufacturing technologies. 3D printers offer product developers the ability to print parts and mechanisms from multiple materials (PLA, ABS, etc.) and with different mechanical and physical properties in a single printing process. The Infill parameter affects the strength and mechanical properties of the resulting 3D object more than others. Therefore, this parameter was investigated in this article, its effect on the strength of the printed part. The work investigated the influence of the filling structure on the mechanical properties of the part and conducted a series of experiments. A total of 5 structures were tested, namely: star, cell, lines, grid and triangle. Using the created equipment described in the article, a series of experiments were conducted. According to the data obtained, it can be concluded that parts filled with triangles and stars have greater mechanical strength than with lines, grids and cells. Also, a higher modulus of elasticity is observed on these fillings. It should also be noted that the results obtained have significant measurement errors. Therefore, the results obtained should be considered only as estimates. To obtain results that can be used for studies using quantitative characteristics, specialized equipment should be used. Also, the issue of anisotropy of the characteristics of the obtained samples requires further study.
Influence of 3D Printing Samples Filling Structure on Their Strength
А. Гуда: ORCID 0000-0003-1139-1580
Keywords: структура заповнення деталі; 3D print; part filling structure; КІТС; TECHNOLOGY